The Politics of Public Finance Al-Mawardi’s Perspective: Al-Ahkam As Sulthaniyah - Muhammad Ali Imran Caniago; Usman Shabur; Ibi Satibi (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
This study aims to explore the concept of Al-Mawardi's public loan. This type of research is qualitative with an exploratory approach. Data collection uses the library method. Primary data was obtained from the book Al-Ahkam As Sulthaniyah and secondary data was obtained from several scientific journals and books related to this research. The analysis used is a qualitative analysis involving descriptive and interpretive data exploration. The results of the study show that the book Al-Ahkam As Sulthaniyah discusses state income, state expenditure, and the Baitul Mal. State revenue comes from zakat, ghanimah, and fai'. The state is only allowed to spend the treasures of the baitul mal as long as these expenditures are used for the public good. Al-Mawardi divided the two objectives of allocating Baitul Mal funds: first, for maslahah (benefit) and arfaq (provision of public facilities). Second, for the mandatory function. If the government has an obligation that is a mandatory function, while the funds in the baitul mal are empty, the government may make public loans because it is feared it will cause state chaos. And this policy was never carried out by the Prophet. If the leader dies, the next leader is responsible for repaying the loan.